MATURITY STAGES OF INDIAN OIL-SARDINE, SARDINELLA LONGICEPS VAL., WITH NOTES ON INOiDElJCE OF ATRETIC FOLLICLES IN ADVANCED OVARIES - Raja, B T Antony (Indian Journal of Fisheries, 2011)
WORKERS engaged in research on the maturity and spawning conditions offish have prepared different types of maturity scale according to the peculiarities presented by different fishes studied by them. Except for a few remarks about the external appearance of ovaries belonging to stages V to VII by Devanesan (1942), there is no detailed account of the different stages of maturity for Sardinella longiceps. Nair (1959) has adopted the maturity scale prepared by the International Coij^cil for the Exploration of the Sea for investigations on oil-sardine. However, when studies on the maturity and spawning habits of oil-sardine were taken up by the author, the absence of a detailed classification was keenly felt and since the International key was found to be not adequate enough to distinguish the different stages, it was considered necessary to prepare a detailed scale for the guidance of workers both in the laboratory and the field so that confusion in the interpretation and assignment of the stages of maturity can be avoided and a uniformity in . eporting achieved